Optimization of Tensile-Shear Strength in the Dissimilar Joint of Zn-Coated Steel and Low Carbon Steel - Sukarman Sukarman; Amri Abdulah; Jatira Jatira; Dede Ardi Rajab; Rohman Rohman; Choirul Anwar; Yulfian Aminanda; Muhammad Ali Akbar (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2020)
The present study features analytical and experimental results of optimizing resistance spot welding performed using a pneumatic force system (PFS). The optimization was performed to join SECC-AF (JIS G 3313) galvanized steel material with SPCC-SD low carbon steel. The SECC-AF is an SPCC-SD (JIS G 3141) sheet plate coated with zinc (Zn) with a thickness of about 2.5 microns. The zinc coating on the metal surface causes its weldability to decrease. This study aims to obtain the highest tensile-shear strength test results from the combination of the specified resistance spot welding parameters. The research method used the Taguchi method using four variables and a combination of experimental levels. The experimental levels are 2-levels for the first parameter and 3-levels for other parameters. The Taguchi optimization experimental results achieved the highest tensile-shear strength at 5049.64 N. It properly worked at 22 squeeze time cycles, 25 kA of welding current, and 0.6-second welding time and 12 holding-time cycles. The S/N ratio analysis found that the welding current had the most significant effect, followed by welding time, squeeze time, and holding time. The delta S/N ratio values were 1.05, 0.67, 0.57 and 0.29, respectively.